A simplified method to improve water distribution and application uniformity for sprinkler irrigation on sloping land: adjustment of riser orientation - Xin Hui (IWA Publishing, 2021)
To improve the water application uniformity for sprinkler irrigation on sloping land, indoor tests were conducted on an artificial slope (slopes of 0, 0.05, 0.10 and 0.15) to evaluate the effects of two riser orientations, vertical (VO) and perpendicular (PO) to the slope, on the uniformity of sprinkler rotation, radius of throw, water distribution of an individual sprinkler and the overlapped water application uniformity (WAU). Compared with the VO, the PO could effectively improve the water distribution on sloping land and minimize the risk of soil erosion. Additionally, the PO was superior in the WAU, and a rectangular arrangement could dramatically enhance the WAU at smaller sprinkler spacing, while larger acceptable sprinkler spacing was accepted in a triangular arrangement. The riser orientation and sprinkler spacing had the most significant effect on the WAU, followed by the slope and sprinkler arrangement, suggesting that the adjustment of riser orientation or sprinkler spacing was helpful in improving the WAU. However, from the aspects of investment cost and installation convenience for irrigation projects, the method of PO was recommended. Therefore, when designing the sprinkler irrigation systems on the slope, choosing PO is the simplest and most effective way to achieve good irrigation uniformity. HIGHLIGHTS Riser perpendicular to the slope can obviously improve the water distribution on sloping land and minimize the risk of soil erosion.; The overlapped water application uniformity is superior for riser perpendicular to the slope than for a vertical riser.; Both the riser orientation and sprinkler spacing have the most significant effects on the overlapped water application uniformity.;